A cross sectional observation study on quality of life and cognition in elderly population and their correlation at a tertiary care centre - Motlag, Mrinalini; S., Tony K.; Madavi, Shweta V.; Bhondre, Amol G.; Pandharipande, M. S.; Deshmukh, Deepti (International Journal of Research in Medical Sciences, 2022)
Background: India, the second most populous country is facing demographic transition. cognitive decline is one of the normative changes of aging; however, this may impact both physical and mental health of an individual. Quality of life is one of the measures of successful aging. This study was conducted to correlate the level of cognition and quality of life in elderly population. Our aim was to assess quality of life in geriatric population using OPQOL-35 and to assess cognitive assessment by MOCA and determine correlation of cognitive level with quality of life (QoL). Methods: A cross-sectional observational study was conducted among 110 elderly adults (above the age of 60 years. Montreal cognitive assessment (MoCA) was administered to assess the cognitive level. QoL was assessed by OPQOL-35. Results: Significant positive correlation was noted between quality of life and level of cognition scoring (with correlation coefficient 0.234). Conclusions: The study concluded that the level of cognition and quality of life of elderly adults are in positive correlation with each other. community level screening of elderly for cognitive dysfunction can be made even in resource poor settings. Early identification and referral of elderly with cognitive dysfunction will ensure successful aging.